World practice of providing scientific advice on the development and authorisation of innovative medicines - E. V. Melnikova; O. V. Merkulova; V. A. Merkulov (Биопрепараты: Профилактика, диагностика, лечение)
Current challenges to healthcare, i.e. the emergence of new diseases, lack of therapies for known diseases and life-threatening conditions, identification of patients who do not respond to standard treatment, on the one hand, and the evolution of scientific understanding of disease processes, medicines, therapies, causes of treatment failures, and implementation in clinical practice of innovations related to molecular biology and genetic engineering, on the other hand, create conditions and opportunities for the development of innovative medicinal products. A relatively new class of medicines is based on human cells and tissues (the term used in Russian legislation is biomedical cell products, BCP). However, the inability to accurately predict the efficacy and financial rewards of such medicines for pharmaceutical companies, as well as significant labour and financial costs associated with their development and clinical use, hinder their entry into the market. The aim of the study was to analyse the foreign regulatory setting for the development and launch of human cell- and tissue-based products, as well as approaches of foreign regulatory authorities to scientific advice, which can be drawn upon by the Russian expert authority when providing advice to BCP developers. The paper summarises the results of analysis of regulations establishing the procedure for providing scientific advice by EU, USA, and Russian regulatory authorities, and analyses the advice provided for the human cell- and tissue-based products which are now authorised in the EU and USA. The analysis of advice provided by foreign regulatory authorities shows that the largest number of consultations were given for medicinal products based on genetically modified cells for the treatment of cancer and genetic diseases. The questions were mainly related to the contents of specifications for finished pharmaceutical products, safety evaluation, curtailing of preclinical studies due to the lack of relevant animal/disease models, the number of subjects and efficacy endpoints in clinical studies, assessment of the appearance of replication-competent retroviruses.